Intruder detection using histogram and edge detection algorithms - Tan, Kai Yang (2016)
Nowadays, night vision technology enables a person to be seen in the dark. In the past, night vision was implemented by making use of the infrared spectrum of electromagnetic waves and devices such as image intensifiers. With the growing popularity of digital computing, many digital image processing techniques have been proposed to implement night vision. These techniques can enhance the images captured by ordinary cameras under low light conditions and can be implemented completely in software. The entire project is done by using image processing techniques via OpenCV which run on Linux environment. The challenge of this project focuses on the detection ability of intruder by using a webcam at a fixed position in low light condition.